AduLeT project: leading technology enhanced learning tips - Gonçalves, Vitor (2019)
The European Commission favours the implementation and use of digital content and specially Open Educational Resources (OER) made accessible in higher education. Most of the lecturers have neither the skills nor the time to supply the teaching materials as digital content or OER. Therefore, Advanced Use of Learning Technologies in Higher Education (AduLeT) is a project that has been set up within the European Union Erasmus+programme support, involving seven partners working together from November 2016 to August 2019. This project will provide lecturers with a community to share user experiences that integrate selected teaching methods with technologies and learning objects to solve an educational problem. AduLeT project brings in a Community of Practice (CoP) for lecturers with suitable teaching methods for technology enhanced learning (TEL). One specific requirement is the visualization of a set of category of tools matching with methods, like a matrix of methods and tools that can easily help teachers choosing from them. The lecturer can also find guidelines in the CoP for the effective use of TEL tools according to themethodology he/she plans to use in the learning process.The CoP will also make it possible to get in touch with other lecturers and to share experiences about teaching with TEL tools. In this contribution we will present the main requisites and functionalities implemented to provide the CoP, based on two workshops with the lecturers of the partner countries. We believe that this project could be an excellent support to the teacher, because it will present good practices for the use of appropriate educational technologies, properly conformed with teaching methods applicable to the resolution of problems, difficulties and requisites of common teaching.